Do carotenoid‐based ornaments entail resource trade‐offs? An evaluation of theory and data. (14th May 2018) - Koch, Rebecca E.; Hill, Geoffrey E.
Abstract : Plain Language Summary Abstract: Within the past several decades, resource trade‐offs have emerged as the commonly accepted explanation for how carotenoid‐based coloration links to individual performance. However, the literature on carotenoid signalling is inconsistent in how carotenoid resource trade‐offs are defined, assessed and interpreted. We provide a clear statement of the resource trade‐off hypothesis for explaining the honesty of carotenoid‐based ornaments, its key assumptions and evidence for (or against) each assumption. Focusing on class Aves, we perform a critical assessment of theoretical and empirical evidence for carotenoid resource limitation and for direct physiological benefits of carotenoid pigments to immune and antioxidant performance. We identify important inconsistencies in how data related to physiological function and carotenoid coloration have been interpreted in the light of the resource trade‐off hypothesis, and we suggest directions for future research. A plain language summary is available for this article.